Age-dependent performance of BRAF mutation testing in Lynch syndrome diagnostics - Bläker, Hendrik; Haupt, Saskia; Sieber-Frank, Julia; Seidler, Florian; Winterfeld, Moritz von; Alwers, Elizabeth; Chang-Claude, Jenny; Brenner, Hermann; Heuveline, Vincent; Knebel Doeberitz, Magnus von; Ahadova, Aysel; Hoffmeister, Michael; et al. (International journal of cancer, 2020)
BRAF V600E mutations have been reported as a marker of sporadic microsatellite instability (MSI) colorectal cancer (CRC). Current international diagnostic guidelines recommend BRAF mutation testing in MSI CRC patients to predict low risk of Lynch syndrome (LS). We evaluated the age-specific performance of BRAF testing in LS diagnostics. We systematically compared the prevalence of BRAF mutations in LS-associated CRCs and unselected MSI CRCs in different age groups as available from published studies, databases and population-based patient cohorts. Sensitivity/specificity analysis of BRAF testing for exclusion of LS and cost calculations were performed. Among 969 MSI CRCs from LS carriers in the literature and German HNPCC Consortium, 15 (1.6%) harbored BRAF mutations. Six of seven LS patients with BRAF-mutant CRC and reported age were <50 years. Among 339 of 756 (44.8%) of BRAF mutations detected in unselected MSI CRC, only 2 of 339 (0.6%) BRAF mutations were detected in patients <50 years. The inclusion of BRAF testing led to high risk of missing LS patients and increased costs at age <50 years. BRAF testing in patients <50 years carries a high risk of missing a hereditary cancer predisposition and is cost-inefficient. We suggest direct referral of MSI CRC patients <50 years to genetic counseling without BRAF testing.